I miss my pencil a design exploration - Bone, Martin (Chronicle, 2009)
From the Publisher: What if doorbells used smell instead of sound? What if watches told time more slowly on weekends? Designers at the ground-breaking firm IDEO the most innovative design company in the world push themselves to ask seemingly outrageous questions like these daily as they work to construct the products that shape our lives. Following 12 design experiments conceived by designers at IDEO, I Miss My Pencil takes a voyeuristic look at what designers do daily, might get to do once, and sometimes only hope to do. Each experiment is made real through collaboration, sketching, prototyping, fabrication, and photographing to go beyond the conceptual to the curiously concrete.